UMP bags Green Technology Award at NRIC2010 - UMP, PNC
Universiti Malaysia Pahang (UMP) coveted a gold medal and the “Sustainable Green Technology” award at the National Research & Innovation Competition (NRIC2010) held at Universiti Sains Malaysia (USM), Penang, recently.